The Effect of Implementing Tax Extensification, Tax Intensification, Tax Audit on Tax Revenue at the Tax Office East Medan Pratama Services in 2023 - Juliandi Sahputra; Latersia Br Gurusinga; Sydney Holly (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to determine the level of tax extensification, tax intensification, tax inspection of the East Medan Pratama KPP during the period January – December 2023. The population in this research is tax employees who work at KPP Pratama Medan Timur. The research method used is a non-probability sampling method, namely census sampling. The respondents of this research were Tax Employees who worked at KPP Pratama East Medan, totaling 43 people. The instrument used is the distribution of questionnaires to collect data from the variables Tax Extensification, Tax Intensification and Tax Audit. The data analysis techniques used are validity test, reliability test, descriptive analysis, normality test, multiple linear regression analysis, partial hypothesis test or t test and calculation of the coefficient of determination.